The Phenomenon of Cultural Spirituality: Impact of ISHARI Youth Participation and Their Role in the Community in Rungkut Kidul - Aldiansyah, Muhammad; Murtadho, Muhammad Alfa Choirul; Khoiroh, Himmatul; Nasrullah, Iklil (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
This study aims to analyze the role of youth in the ISHARI community in Rungkut Kidul. Youth is often identified with an individualistic attitude, norm deviations, drugs, and drunkenness. Thus, people often feel uncomfortable and become restless due to the negative actions of young people. Understanding religion to youth needs to be intensified so that they can change negative actions and become more pious to God. Through the ISHARI organization, youth are given a place to remember Allah and Rasulullah through Hadrah art culture. The approach used in this study uses a phenomenological approach and uses the theory put forward by Biddle and Thomas. The role theory in question is the role of the reality of social life, including a social position in society. This study shows significant results in the spiritual and social development of youth around Rungkut Kidul after following the ISHARI routine. The impact felt individual youth began to experience an increase in several critical aspects of life, such as social, economic, and spiritual. In addition, the empathy of the ISHARI Rungkut Kidul youth is relatively high in seeing the problems that occur in the lives of the local community. Thus, the youth who participated in ISHARI received a positive image from the community around Rungkut Kidul.